Biochar-based electrochemical sensors: a tailored approach to environmental monitoring - Zheng, Alvin Lim Teik; Lih, Ellie Teo Yi; Hung, Yiu Pang; Boonyuen, Supakorn; Osman Al Edrus, Syeed Saiful Azry; Chung, Eric Lim Teik; Andou, Yoshito (Springer, 2025)
Biochar (BC), often obtained via thermochemical conversion methods of biomass, has emerged as a versatile material with significant potential in electrochemical sensing applications. This review critically examines the recent advancements in the development of BC-based sensors for the electrochemical determination of pharmaceuticals, pesticides, heavy metals, phenolic compounds, and microplastics. BC-based electrochemical sensors have emerged as a promising alternative due to their sustainability, cost-effectiveness, and excellent electrochemical properties. The unique physicochemical properties of BC, including its high surface area, porosity, and functional groups, contribute to its effectiveness as a sensor material. The review begins with an overview of the synthesis methods for BC, highlighting the activation strategies on its structural and electrochemical properties. Next, the functionalization of BC and its integration into electrochemical sensor platforms are explored. The performance of BC-based sensors is evaluated using electrochemical focusing on their sensitivity, selectivity, detection limits, and stability. Future directions for research are proposed, emphasizing the need for further optimization, miniaturization, and integration of BC-based sensors into portable and on-site analytical devices.